Determinan Pertumbuhan Laba berdasarkan Kinerja Keuangan - Efa Wahyuni; Noor Muhammad Adipati (ARBITRASE: Journal of Economics and Accounting, 2023)
The purpose of this study was to determine the effect of Current Ratio, Net Profit Margin, Total Asset Turnover, Debt to Equity Ratio, Debt to Asset Ratio, Return On Assets on Profit Growth at PT Cisadane Sawit Raya partially. This study uses a quantitative approach. The data analysis technique used in this study is the Kendall tau correlation technique. Based on the results of the study, it shows that there is an effect of the Current Ratio on profit growth at PT Cisadane Sawit Raya. These results are evidenced by the partial test results of Zcount 1.91 ?Ztable 0.9719. There is an effect of Total Asset Turnover on PT Cisadane Sawit Raya's profit growth. The partial test results of Zcount 1.33 ? Ztable 0.4082. There is an effect of Net Profit Margin on PT Cisadane Sawit Raya's profit growth. The partial test results of Zcount 1.33 ? Ztable 0.4082. There is no effect of Debt to Equity Ratio and Debt to Asset Ratio on PT Cisadane Sawit Raya's profit growth. The partial test results are Zcount -1.91 ? Ztable 0.0281 and the partial test results are Zcount -1.91 ? Ztable 0.0281.